Azimuthal variations of oxygen abundance profiles in star-forming regions of disc galaxies in EAGLE simulations. Issue 4 (20th December 2019) - Solar, Martín; Tissera, Patricia B; Hernandez-Jimenez, Jose A
ABSTRACT: The exploration of the spatial distribution of chemical abundances in star-forming regions of galactic discs can help us to understand the complex interplay of physical processes that regulate the star formation activity and the chemical enrichment across a galaxy. We study the azimuthal variations of the normalized oxygen abundance profiles in the highest numerical resolution run of the Evolution and Assembly of GaLaxies and their Environments (EAGLE) Project at $z$  = 0. We use young stellar populations to trace the abundances of star-forming regions. Oxygen profiles are estimated along different line of sights from a centrally located observer. The mean azimuthal variation in the EAGLE discs are ∼0.12 ± 0.03 dex $R_{\rm eff}^{-1}$ for slopes and ∼0.12 ± 0.03 dex for the zero-points, in agreement with previous works. Metallicity gradients measured along random directions correlate with those determined by averaging over the whole discs, although with a large dispersion. We find a slight trend for higher azimuthal variations in the disc components of low star-forming and bulge-dominated galaxies. We also investigate the metallicity profiles of stellar populations with higher and lower levels of enrichment than the average metallicity profiles, and we find that high star-forming regions with high metallicity tend to have slightly shallower metallicity slopes compared with the overall metallicity gradient. The simulated azimuthal variations in the EAGLE discs are in agreement with observations, although the large variety of metallicity gradients would encourage further exploration of the metal mixing in numerical simulations.